Influence of Chronic Alcohol Consumption on Inward Rectifier Potassium Channels in Cerebral Arterioles - Sun, Hong (2007)
Inward rectifier potassium (K(IR)) channels appear to play an important role in the regulation of cerebral blood flow. Our goal was to examine the influence of chronic alcohol exposure on K(IR) channels in cerebral arterioles. Sprague-Dawley rats were fed liquid diets with or without alcohol for 8–12 weeks. Using intravital microscope, we measured diameter of pial arterioles in response to an inhibitor, BaCl(2), and an activator, KCl, of K(IR) channels in the absence and presence of a scavenger of reactive oxygen species, tempol, or an inhibitor of NAD(P)H oxidase, apocynin. Application of BaCl(2) (30 and 100 μM) produced dose-related vasoconstriction in nonalcohol-fed, but not in alcohol-fed rats. In addition, application of KCl (3, 10, and 30 mM) produced dose-related dilation in nonalcohol-fed and alcohol-fed rats, but the magnitude of vasodilatation was less in alcohol-fed rats. In contrast, nitroglycerin-induced vasodilation was similar in nonalcohol-fed and alcohol-fed rats. Superfusion of cranial window with tempol (0.1 mM) or apocynin (1 mM) did not alter baseline diameter and nitroglycerin-induced dilation of pial arterioles in nonalcohol-fed and alcohol-fed rats, but significantly improved impaired KCl-induced dilation in alcohol-fed rats. Our findings suggest that chronic alcohol consumption impairs the role of K(IR) channels in basal tone and KCl-induced dilation of cerebral arterioles. In addition, impaired KCl-induced dilation of cerebral arterioles during alcohol consumption may be related to enhanced release of oxygen-derived free radicals via NAD(P)H oxidase.